HUBUNGAN FAKTOR KETERCUKUPAN AIR BERSIH DAN TINGKAT SOSIAL EKONOMI DENGAN KEPEMILIKAN JAMBAN SEHAT DI DESA ABI KECAMATAN OENINO KABUPATEN TIMOR TENGAH SELATAN. - Haryati Boimau, Curniasti Duhitantia; Nurjazuli, Nurjazuli; Wahyuningsih, Nur Endah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Abi is one of the villages with the lowest percentage of healthy latrines ownership compared to other in Oenino Subdistrict.There are 46 household (18,5%) that have access to healthy latrines in Abi village. The purpose of this study was to analyze what factors influence the ownership of healthy latrines in Abi Village Oenino District of Timor Tengah Selatan. This study is an observational study using a cross sectional design, as more as 78 respondents taken with simple random sampling techniques. Independent variables studied (knowledge, attitudes, socioeconomic level, clean water adequacy, role of village governments, and the role of health officers) and dependent variables (healthy latrines ownership). The collected data would be analyzed chi-square test. The results showed that 51,3% low public knowledge, 51,3% had a negative public attitude,69,2% low socio-economic level of society, 56,4% of clean water need were not fulfilled, 39,7 did not receive support from the village government, 53,8% did not receive support from health workers. There is a relationship between knowledge and the ownership of healthy latrines (p =0.007), attitude (p=0.002), sosioeconomic level (p=0.002), the adequacy of clean water (p=0.000), the Role of Village Government, (p=0.026), The Role of Health officers (p=0.011). The low ownership of healthy latrines in Abi village is influenced by factors of low socioeconomic level and adequacy of water needs because clean water sources are far away and limited clean water reservoirs.